Using MatLab-Simulink for simulating load compensation in four-wire electrical power systems - De Oliveira, Luis Carlos Origa [UNESP]; Barros Neto, Manoel C. [UNESP]; De Souza, Júlio Borges [UNESP] (My University, 2004)
This work describes a method of power factor control and correction of the unbalanced currents in four-wire electrical circuits. This method is based on the insertion of two compensation networks, one wye-grounded neutral and another in delta, in parallel with the load. The mathematical development has been proposed in previous work. In this paper, however, the method has been adapted to accept generic power factors for the system to be compensated. On the other hand, the determination of the compensation susceptances is based on the instantaneous values of the load currents. The results are obtained using the MatLab-Simulink environment and the validation of the achieved results are verified. ©2004 IEEE.
Keywords: Power factor; Reactive power compensation; Unbalances